A bibliometric analysis of current research, development status, and future development trends of soy and whey proteins - Li, Meng-jie; Feng, Duo; Ma, Meng-han; Han, Di; Li, Hu; Li, Na; Liu, Tian-xin; Fan, Jia-yu; Wang, Jing (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to analyse the current status and development of research on soy and whey proteins during the period 2004–2024 using bibliometric methods in order to reveal the research hotspots and development trends in this field.MethodsThe study used CiteSpace and VOSviewer software to visualise and analyse 1,888 articles in the core database of Web of Science, including collaboration mapping, co-occurrence mapping, and co-citation mapping, in order to detect the development of disciplinary knowledge areas, research hotspots, frontiers, and trends.ResultsThe study found an overall fluctuating increase in the publication of relevant literature, especially a significant increase between 2016 and 2023. China has the most prominent research contribution in this field and maintains close collaboration with several countries. Keyword analysis revealed that research hotspots include antioxidant properties, sodium caseinate, pH effects, and colorectal cancer, and that research is gradually changing from process physicochemical properties to nutritional health. However, there were some limitations in this study, such as the narrow subject matter of the dataset, some high-quality literature may not be valued due to low citation rates, and there was a delay in updating the database, which affected the timeliness of the analysis.ConclusionOver the past two decades, research on soy and whey proteins has witnessed a shift from processing aspects to nutrition and health, reflecting the emphasis and in-depth exploration of the nutritional and health values of proteins. Despite its limitations, this study provided a valuable reference for researchers in the field of soy and whey proteins, helping them to grasp the direction of their research and rationally allocate resources. At the same time, it also provided data support for policymakers to formulate relevant research policies and promote international cooperation, which will help to promote the further development and innovation of proteins in the field of nutrition. Therefore, it was recommended that research institutes strengthen their cooperation and work together to meet future research challenges and promote the sustainable development of proteins in nutrition.